THE PARTIAL SOLUTION FOR THE OPTIMIZATION OF THE GEOMETRICAL SHAPE OF BUNKERS AND SILOS - Bannikov, D. O. (Science and Transport Progress, 2007)
In the paper analytical solutions for optimization of external geometrical shape according to criteria of massminimum of bunker and silo capacities for granular materials are presented. The special case of two-parted construction with the vertical upper part was considered. The method of transformation to the problem with one unknown symbol was used. The given solutions are compared with solutions, which were obtained by the author according to the Lagrange method of uncertain multiplies.